EFFECTIVENESS OF CONSERVATIVE MYOMECTOMY FOR PRESERVATION OF WOMEN'S REPRODUCTIVE CAPACITY (World Science, 2025)
Over the past few years, the population of Ukraine has faced a number of traumatic events. These events have a negative impact on the life of all Ukrainians and cause an increase in the frequency and severity of stress disorders. However, the biggest shock was the beginning of the active phase of the war in February 2022 in Ukraine. Women develop post-traumatic stress disorder (PTSD) under the influence of super-extreme situations. Amidst stress and PTSD, women experience changes in hormonal levels, immune status, and reproductive health issues.According to current data, about 30% of people exposed to traumatic events will have PTSD and need help. As for the female population, about 10% of adult women and 7% of girls are diagnosed with PTSD in their lifetime. It is also known that women experience PTSD almost 1.5 times more often than men. The prevalence of mental disorders is particularly high among internally displaced persons. In particular, in this cohort, 22% of men and 36% of women develop and are diagnosed with PTSD.According to WHO, the problem of uterine tumour processes is one of the most important areas of modern medicine. According to the International Classification of Diseases, 10th Revision (ICD-10: D25.0-D25.9), uterine leiomyoma (UGC), as one of the most common tumours of the female reproductive system, ranks among the top gynaecological diseases (GD) and is combined with extragenital (EGD) and genital (GC) pathologies. Studies conducted in recent years have shown that the incidence of LM has shown an upward trend in recent decades and is 35-45% in women over the age of 30. According to scientists, the true incidence of breast cancer is as high as 77%. The incidence of recurrent LM after reconstructive surgery ranges from 2.6 to 50 % of cases. Studies have shown that in 18.0% of patients of early reproductive age, after myomectomy, newly emerging myomatous nodes were detected. The analysis of the results allowed us to conclude that myoma recurrence is 1.2 times more likely to occur in a subgroup of patients with PTSD. It was also found that myoma recurrence occurs mainly in the first two years after surgery.